Schema modes in eating disorders: an interpretative phenomenological analysis - Bowker, Chantal Ann (Rhodes University, Faculty of Humanities, Department of Psychology)
The DSM-5 prevalence rate of anorexia nervosa is 0.4%, bulimia nervosa is 1% to 1.5%, and binge eating disorder is 1.6% (American Psychiatric Association, 2013). Although treatment approaches for eating disorders have high drop-out rates and low rates of recovery, treatment modalities that address childhood factors contributing to the eating disorder, as well as the eating disorder behaviours, have better outcomes. Schema therapy is an integrative approach that has been used for the treatment of eating disorders for more than a decade. Central features in schema therapy include the identification of early maladaptive schemas arising from unmet needs and schema modes. Schema modes, composed of schemas and coping mechanisms, are active for an individual at a particular time in response to triggers in the environment (Brown et al., 2016). Identifying an individual's modes is a crucial aspect that reflects the underlying structure of the individual's creation of reality. A phenomenological understanding of the modes is essential for developing a case conceptualisation and treatment plan. Differences exist in the naming and description of modes in the current schema therapy literature, which suggests the need for a phenomenological investigation of these structures. This research study used a mostly qualitative approach, in the form of clinical interviews, substantiated by questionnaires, to examine schema modes. Case presentations using the schema therapy model are provided for five women with either anorexia nervosa, bulimia nervosa or binge eating disorder. Then, through a process of interpretative phenomenological analysis, specific modes are examined as to how they are experienced by the participants and influence their behaviour. The features of schema modes in these clinical cases are compared to the existing literature to extend the understanding of schema modes in eating disorders. The participants' experiences revealed that they had schema modes in common, regardless of the eating disorder presentation, but that the features of the individual modes varied. Modes found in the current literature such as the Detached Self-Soother and Perfectionist Overcontroller coping mode, were found in all the participants. Four of the five participants had an Eating Disordered Overcontroller mode. Features consistent with the existing descriptions of the Perfectionist Overcontroller, Eating Disordered Overcontroller and Detached Self-Soother modes were noted, and new features were identified. The Perfectionist Overcontroller and Eating Disordered Overcontroller have been presented here as complex composite modes with sub-modes that work together in a coherent way in the service of the same project (Edwards, 2020b). Twenty-three features are identified in the parent modes. Blended parent modes, with multiple features active in a situation, were described. The blended parent modes expand on the existing literature on parent modes. The findings in this research support and extend the mode structure identified in the schema therapy theory, and highlight the idiosyncratic nature of the modes.
Keywords: Eating disorders; Anorexia nervosa; Bulimia; Compulsive eating; Schema-focused cognitive therapy; Interpretative phenomenological analysis (IPA)